2012
DOI: 10.1159/000342390
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid Independently Predicts Cardiovascular Events in Advanced Nephropathy

Abstract: Background: Chronic kidney disease (CKD) is associated with increased risk for cardiovascular (CV) disease and is also associated with elevated uric acid, which is emerging as a nontraditional CV risk factor. We therefore evaluated uric acid as a risk factor for CV disease in subjects presenting to nephrologists with CKD who were not on medications known to alter endothelial function. Methods: 303 subjects with stage 3–5 CKD were followed for a mean of 39 months (range 6–46) and assessed for fatal and nonfatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(41 citation statements)
references
References 74 publications
2
36
0
3
Order By: Relevance
“…118,119 Moreover, Madero et al 3 found that CKD patients with high serum UA concentration had a higher risk for all-cause and CV mortality. Similar, Kanbay et al 120 reported that HUA predicts CV events in advanced CKD stages. In accordance, Liu et al 116 suggested that HUA is a risk factor for all-cause and CV events but not for renal outcomes in stages 3-5 CKD patients.…”
Section: Hua and CV Mortalitysupporting
confidence: 56%
“…118,119 Moreover, Madero et al 3 found that CKD patients with high serum UA concentration had a higher risk for all-cause and CV mortality. Similar, Kanbay et al 120 reported that HUA predicts CV events in advanced CKD stages. In accordance, Liu et al 116 suggested that HUA is a risk factor for all-cause and CV events but not for renal outcomes in stages 3-5 CKD patients.…”
Section: Hua and CV Mortalitysupporting
confidence: 56%
“…In addition to causing gouty arthritis (12), the risk of asymptomatic HUA is closely related to T2DM, hypertension, metabolic syndrome, cerebral stroke, and cardiovascular diseases (13)(14)(15)(16). Recent studies have shown that the serum uric acid level is closely related to macrovascular complications in T2DM patients (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Uric acid has been recently implicated in the causation of renal disease, hypertension, and coronary artery disease. [22][23][24] This new paradigm of causation has distinct pathophysiologic pathways different from classical uremic nephropathy, which traditionally described in the setting of tumor lysis syndrome and severe gouty arthritis. [25][26][27] Compelling experimental data and several observational and epidemiologic studies showed a strong association of kidney damage and elevated serum uric acid levels.…”
Section: Discussionmentioning
confidence: 99%